Politeness Strategies Employed by the Main Characters of Lauren Weisberger’s Movie: “The Devil Wears Prada” - Nadia Probosini (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2020)
This research was an interpersonal communication study on politeness strategies employed by the main characters in Devil Wears Prada movie in the context of workplace communication. This research aimed to explain politeness strategies employed by the main characters of The Devil Wears Prada movie. This was qualitative research, and the data were utterances of the three main characters containing politeness strategies. The source of the data was the script of Devil Wears Prada movie, and it was found that 135 politeness strategies occurred. It was: Bald On Record (47 times), Positive Politeness (49 times), Negative Politeness (19 times), and Off Record (20 times). The findings demonstrated that positive politeness strategies were the most frequent strategies in this movie. It indicated that the main characters tended to use positive politeness to show their respect and that they have a harmonious relationship in the workplace.